Prescription of red cell concentrates by emergency physicians - Faria,João Carlos Pina (2020)
SUMMARY OBJECTIVE To evaluate the adequacy of the prescription of red cell concentrates by emergency physicians. METHODS A cross-sectional study based on the survey of transfusion requests records completed by emergency physicians, from May/2018 to April/2019, in an emergency hospital. Adequacy in the indication, volume, and subtype (filtered, irradiated, and washed) of prescribed erythrocytes were evaluated. To compare the qualitative data, we used the χ2 test. The significance level adopted was 5%. RESULTS One thousand and twenty-two transfusions were evaluated. The indication, volume, and subtypes were correct in 72.7%, 45.9%, and 81.6% respectively. Transfusion in symptomatic patients presented superior adequacy when compared to asymptomatic individuals with significant statistical difference (indication: 79,6% vs 67.2%, p <0.001; Volume: 63.5% vs 31.7%, p <0.001; subtype: 85.3% vs 78.7%, p 0.006). Among clinical situations, there were more errors in sepsis (39.7%) and pneumonia (36.3%). More than half of the prescriptions presented excessive volume, raising the risk of circulatory overload, observing that the mean age was 60.6 years. The specific analysis of the prescribed subtypes showed adequacy of 17.9% in the filtered, 1.7% in the irradiated, and none in the washed. Thirty transfusions should have been filtered, but the prescriber did not request the subtype. CONCLUSION One hypothesis for the observed inaccuracies is inadequate medical training on the subject, both in undergraduate and medical residency, associated with a lack of continuing education on transfusion protocols. The transfusion Committee received the results of this study with a proposal for continuing education measures on transfusion hemotherapy.